Analisis Pengaruh Literasi Keuangan, Financial Technology, dan Demografi terhadap Inklusi Keuangan pada Masyarakat di Kota Surabaya - Adinda Novita Sari; Achmad Kautsar (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2020)
Financial inclusion is one of the interesting discussions in global economic development. Indonesia is a country in ASEAN which has the most rapid increase in financial inclusion in recent years. In the era of the industrial revolution 4.0, everyone is required to be able to follow the development of existing technology and information. This study aims to determine the influence of independent variables (financial literacy, financial technology, demographics) on the dependent variable (financial inclusion) in the City of Surabaya. This study is a causality study with quota sampling. The data of this study is quantitative by collecting data by questionnaire. The data analysis technique used is multiple linear regression. The result of this study based on t statistical tests show that financial literacy, age, and education have a positive effect on financial inclusion. While the variables financial technology, gender, and income did not affect on financial inclusion. Based on the statistical test f, all of the independent variables simultaneously influence the dependent variable (financial inclusion).